2021
DOI: 10.3390/mi12030260
|View full text |Cite
|
Sign up to set email alerts
|

Dry Film Photoresist-Based Microfabrication: A New Method to Fabricate Millimeter-Wave Waveguide Components

Abstract: This paper presents a novel fabrication method based on dry film photoresists to realize waveguides and waveguide-based passive components operating at the millimeter-wave frequency (30–300 GHz). We demonstrate that the proposed fabrication method has a high potential as an alternative to other microfabrication technologies, such as silicon-based and SU8-based micromachining for realizing millimeter-wave waveguide components. Along with the nearly identical transfer of geometrical structures, the dry film phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…During the optimization of all the sensitive parameters, ± 10 µm pin height tolerance has been considered also. From our previous experiments on SUEX dry film photoresist the achieved fabrication tolerance was ± 2 µm [14]. Thus, the designed T-junction power divider is expected to perform well after manufacturing.…”
Section: Design Of the Proposed Power Dividermentioning
confidence: 94%
See 1 more Smart Citation
“…During the optimization of all the sensitive parameters, ± 10 µm pin height tolerance has been considered also. From our previous experiments on SUEX dry film photoresist the achieved fabrication tolerance was ± 2 µm [14]. Thus, the designed T-junction power divider is expected to perform well after manufacturing.…”
Section: Design Of the Proposed Power Dividermentioning
confidence: 94%
“…Dry film photoresist on the other hand can overcome all abovementioned fabrication issues. Recently SUEX dry film photoresist has been used to fabricate waveguide components operating above 200 GHz [14], verifying that dry film photoresist not only delivers superior geometrical features and fabrication tolerances, but also reduces the processing time and the production cost.…”
Section: Introductionmentioning
confidence: 98%
“…Due to its unique advantages of uniform thickness, controllable, stability, high reliability, easy operation, low energy of exposure and high resolution, DFRs has developed rapidly, and has been widely utilized in PCB manufacturing process. [105][106][107][108] As displayed in Figure 28, the polyester (PET) film, photoresist layer and polyethylene (PE) film from bottom to top together constitute a complete DFRs. [109] The PET film plays the role of bearing photoresist layer, and PE film is used to avoid the deterioration caused by the contact between photoresist layer and dusts or oxygen, in addition, prevents adhesion between multilayer film.…”
Section: Pcb Dry Film Photoresistmentioning
confidence: 99%
“…[15] S. Farjana et al presented a novel fabrication method based on dry film photoresists to realize waveguides and waveguide-based passive components operating at the millimeter-wave frequency (30-300 GHz). [16] M. Nilsen et al reported the use of commercially available dry film photoresists (5 μm thick) onto prepatterned silicon substrates that contain atomic force microscopy compatible probe bodies. [17] To elucidate the effectiveness of the fabrication method based on dry film photoresist further, here we use a commercial Riston FM800 photopolymer film (DuPont de Nemours, Inc., USA) to fabricate the high-performance micromixer.…”
Section: Introductionmentioning
confidence: 99%
“…presented a novel fabrication method based on dry film photoresists to realize waveguides and waveguide‐based passive components operating at the millimeter‐wave frequency (30‐300 GHz). [ 16 ] M. Nilsen et al . reported the use of commercially available dry film photoresists (5 μm thick) onto prepatterned silicon substrates that contain atomic force microscopy compatible probe bodies.…”
Section: Introductionmentioning
confidence: 99%